Thin silicon solar cells with SiОх /SiNx Bragg mirror rear surface reflector - Ivanov, I.I.; Nychyporuk, T.V.; Skryshevsky, V.A.; Lemiti, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
. Bragg reflectors consisting of sequence of dielectric layers with a quarter wavelengths optical thickness are promising to create solar cells of third generation. SiОх /SiNx Bragg mirror (BM) at the backside of textured multicrystalline silicon solar cells was fabricated by PECVD method. BM with 9 bi-layers was optimized for the maximum reflectivity within the wavelength range Δλ = 820...1110 nm. The maximum measured reflectivity is approximately 82 %. Measured reflectivity values were compared with the simulated ones by using the transfer matrix. Effect of parameters for pyramids of several types on the total reflectivity of BM deposited on textured silicon surface was simulated. Enhancement of light absorption and external quantum efficiency in the longwave part of the spectrum (λ > 940 nm) was observed, and it was explained as increase of the photon absorption length. The influence of BM on passivation of SC rear surface was explored. The cell back contact was formed by Al diffusion through BM to the μc-Si wafer and promoted by a pulsed laser. For SC with BM, the efficiency 13.75 % is obtained comparatively with efficiency 13.58 % for SC without BM.